?????? ???? ?????? ?????????? ????? ???? ???????????? ?????????? ????????????? ????????????? ?????? ????????? - ????????, ?.?. (FAN, TA’LIM VA AMALIYOT INTEGRATSIYASI, 2023)
The problem of a creativity of the modern person becomes more and more actual. Creative persons are necessary to a developing society, first of all, - for being intellectual-creative, capability to think safely, creativity - it is nonconventional and original, solving problems productively. The creative persons are creatively proving in different kinds of activity are necessary for a modern society. Today creativity - the important criterion of the person, the factor of its complete development. There fore in the state educational policy of creativity - at intellectual level, naturally, on an informative basis, the especial attention now is given to active creativity. In the educational policy of Uzbekistan among development of the basic qualities and abilities trained are allocated creative - creative potential of the person. With especial attention to is intellectual-creative thinking. That is quite lawful, as the new thinking - courageous, original, creative, initiative, constructive, is innovative-innovative today is required.